Efficacy of microbial approaches in controlling Ganoderma boninense pat and their effect on soil microbial diversity - Arnnyitte Alexander (2014)
Basal Stem Rot (BSR) is the most destructive disease of oil palm (Elaeis guineensis Jacq.) which caused by bracket fungus; Ganoderma boninense . With no remedy to date, this disease has jeopardized the industry of oil palm critically. Several approaches including cultural, chemical, mechanical and biological measures have been reported in attempt to control this disease, but unfortunately, none have given satisfactory result. Therefore, a more reliable approach that could manage this disease, besides a continuous and sustainable oil palm production is worth to be further investigated. Introduction of microbes in disease management have been used for decades. An astute observation of low incidence of disease due to Ganoderma pathogen in natural ecosystem suggests that a healthy natural ecosystem can hinder the incidence of Ganoderma pathogen outbreak. In this respect, study on the potential of microbes in suppressing the growth of Ganoderma boninense and its effect to the soil microbial diversity were investigated in this project. Three microbes-based products which are Living Soil Microbes (LSM), Agrinos (AGN) and Agriorganica (AO) were tested in this study. LSM contains multi-strain of Bacillus spp. and Trichoderma spp., whereas AGN consist of Bacillus spp., Pseudomonas spp. and Aspergillus sp. Meanwhile, AO comprises of three living food microbes which are Lactobacillus, Nattobacillus and Saccharomyces cerevisiae developed from Japanese fermentation and brewing technology. To examine the ability of the treatments in reducing BSR disease incidence, assessments in nursery and field trial were conducted. The results from both trials showed that LSM, AGN and AO were able to reduce the colonization of G. boninense based on the reduction of ergosterol content compared to untreated control. Based on the nursery results in prevention of Ganoderma colonization trial, after two months interval, LSM and AO showed greater reduction of ergosterol content with 1.991 μg g-1 and 1.994 μg g-1 respectively, however LSM recorded the lowest Disease Incidence (DI) with only 30%. After four months interval, LSM and AGN showed greater reduction in ergosterol content with 2.261 μg g-1 and 2.214 μg g-1 respectively, however, AGN and AO had the lower DI with 60%. Meanwhile, based on the results in suppression of Ganoderma colonization trial, after two months of interval, all treatments successfully reduced the ergosterol content and DI within the time frame. After four months interval, all treatments showed an increment in DI, however, LSM had the lowest ergosterol content which is 2.388 μg g-1. Meanwhile, assessment in the field trial showed that both LSM and AO had significantly reduced the amount of ergosterol to 0.663 μg g-1 and 1.817 μg g-1. Both LSM and AO also successfully reduced the DI down to 12% and 24% respectively. The effect of the application of microbial products to the soil microbial community was evaluated based on the isolation using Colony Forming Unit (CFU) and later identification using Biolog and molecular techniques. The numbers of CFU for bacteria and yeast after application of these microbes remain unchanged, which were varied between 104 to 106 cfu/g and 102 to 105 cfu/g of soil respectively. However, the number of CFU for fungi was increased up to 104 cfu/g of soil. Identification based on Biolog and sequence homology technique shows that new species arose and overcome the predominated species after application of these microbes. The new identified species were Enterobacter spp., Microbacterium spp., Burkholderia spp., Yarrowia spp., Paecilomyces spp., Neosertoya spp. etc. In vitro antagonistic assay of microbial treatments showed that only LSM has the activity against G. boninense (Percentage Inhibition of Radial Growth, PIRG=70%). Observation under Scanning Electron Microscopy (SEM) showed that Ganoderma mycelium was highly disrupted and lysed after exposure to LSM treatment. Potential bioactive component produced by LSM during this interaction which inhibiting the growth of G. boninense was further investigated via Reverse Phase- High Performance Liquid Chromatography (RP-HPLC) and Liquid Chromatography Mass Spectrometry (LCMS). Several potential antimicrobes compounds were detected including Pyrene-1,6-dione, 12-Deoxyaklanonic acid, N-Methyl-aaminoisobutyric acid, 4-O-8’,5”-5’-Dehydrotriferulic acid, Halstoctacosanolide A, N-acetyl-leu-leu-tyr-amide, Methenamine, 12-oxo-10Z-dodecenoic acid, Gly-Met-OH and Lovastatin. These metabolites may probably contribute on the antagonistic effect of LSM microbes against G. boninense . This study showed that the use of biological control agents (BCAs) give promising results in controlling G. boninense under different level and environment. The use of BCAs could offer an alternatives for the use of fungicide and it may well be worth to be looked in more detail into the potential of BCAs for its future prospects in agriculture.